Chiral separation of styrene oxides supported by enantiomeric tetrahedral neutral Pd(II) cages - Rajasekar, Prabhakaran; Pandey, Swechchha; Ferrara, Joseph D.; Del Campo, Mark; Le Magueres, Pierre; Boomishankar, Ramamoorthy (Inorganic Chemistry, 2019)
The separation of enantiomers is of considerable importance in the preparation of the compounds of biological interests, catalysis, and drug development. Here, we report a novel enantioseparation of styrene epoxides (SOs) resolved in the presence of a pair of enantio-enriched tetrahedral cages. Chiral neutral cages of formula [(Pd3X*)(4)(C6O4Cl2)(6)] ([X*](3-) = RRR-or SSS-[PO(N(*CH(CH3)Ph)(3)](3)) are constructed from Pcl, building units supported by tris(imido)phosphate trianions and chloranilate linkers. These cages exhibit considerable enantioselective separation capabilities toward a series of styrene epoxides via a crystallization inclusion method. A highest enantiomeric excess (ee) value of up to 80% is achieved for the (R)-4-fluorostyrene oxide.